2016
DOI: 10.1039/c5cp05465f
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high-frequency ultrasound on nanocomposite microcapsules: in silico and in situ visualization

Abstract: The impact of high-frequency (1.2 MHz) ultrasound with a power density of 0.33 W cm(-2) on microcapsule nanocomposite shells with embedded zinc oxide nanoparticles was investigated by exploring modeling simulations and direct visualization. For the first time the sonication effect has been monitored in situ on individual microcapsules upon exposure of their aqueous suspension to ultrasound. The stress distribution on the microcapsule shell for the impact of ultrasound with high (1.2 MHz) and low (20 kHz) frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…35 In one study, the release of bovine serum albumin from PSS/PAH capsules with embedded Au nanoparticles was triggered by low-intensity, high-frequency US at 3.19 W after 10 min of sonication. 36 Computational simulations by Korolovych and co-workers on multilayer capsules revealed that 75% of PSS/PAH capsules modified with ZnO nanoparticles could be successfully destroyed by only 23 mW (0.33 W/cm 2 ) US for 3 s. 37 However, the inclusion of nanoparticles complicates capsule synthesis and might challenge capsule biocompatibility and biodegradability. Very recently, in situ carbonization of dextran molecules within a (PSS/PAH) 4 shell at 160 °C has been shown to result in fluorescent carbon dots, which gave the capsules cytocompatibility, ultrasound responsiveness, reduced permeability, and good fluorescent stability.…”
mentioning
confidence: 99%
“…35 In one study, the release of bovine serum albumin from PSS/PAH capsules with embedded Au nanoparticles was triggered by low-intensity, high-frequency US at 3.19 W after 10 min of sonication. 36 Computational simulations by Korolovych and co-workers on multilayer capsules revealed that 75% of PSS/PAH capsules modified with ZnO nanoparticles could be successfully destroyed by only 23 mW (0.33 W/cm 2 ) US for 3 s. 37 However, the inclusion of nanoparticles complicates capsule synthesis and might challenge capsule biocompatibility and biodegradability. Very recently, in situ carbonization of dextran molecules within a (PSS/PAH) 4 shell at 160 °C has been shown to result in fluorescent carbon dots, which gave the capsules cytocompatibility, ultrasound responsiveness, reduced permeability, and good fluorescent stability.…”
mentioning
confidence: 99%
“…Zinin et al calculated the natural vibrations of the specific types of bacteria. [132] The polymer/zinc oxide nanoparticle microcapsule shells were destroyed by ultrasound treatment more effectively at high-frequency ultrasound in comparison to the low-frequency one with the same power density. The natural frequencies and corresponding qualities were calculated for specific types of bacteria using data about mechanical properties and thickness of cell shell.…”
Section: Control Over Us Sensitivity Of Microcapsules By Mechanical Pmentioning
confidence: 96%
“…It leads to the highest impact of ultrasound on the hydrophobic modified surface in comprising with hydrophilic surface. [132] Nowadays, A number of new approaches for in vivo visualization and treatment using ultrasound such as HIFU [133][134][135] and PA imaging [136,137] are rapidly growing. [129] The hydrophobic surfaces were made using imprinting method, [128] but recently an original approach was demonstrated using consequently adsorption hydrophilic PE molecules and hydrophobic nanoparticles.…”
Section: Ultrasound Triggeringmentioning
confidence: 99%
See 2 more Smart Citations